Evaluating technology transfer and the performance of manufacturing SMEs - Jabar, Juhaini; Soosay, Claudine (2011)
Technology acceptance model (TAM) although pertinent in technology alliances, has received very little attention in the literature on collaborations. This research examines technology alliances formed by Malaysian manufacturing SMEs for technology acquisition and their performance outcomes. This research adopts two of TAM’s constructs (relative advantage and ease of use) to examine their relationships with organisational performance; with STA as a mediator. Results are established through survey data from 242 manufacturing SMEs and analysed using structural equation modelling. Our findings establish that forming STA is crucial in enhancing organisational performance. This study provides consideration for Malaysian manufacturing SMEs in enhancing their technological capabilities so as to sustain competitiveness and accelerating the industrialisation of the nation.